The answer is (f o g)(x) = 2x^2 - 13
In order to find a composite function, you take the first letter (in this case f) and use that equation. You then remove the variable and put in the second letter (g).
f(x) = 2x + 1 ----> Remove variable.
f(x) = 2( ) + 1 ----> Insert g(x)
(f o g)(x) = 2(x^2 - 7) + 1 ----> Distribute
(f o g)(x) = 2x^2 - 14 + 1 ----> Simplify
(f o g)(x) = 2x^2 - 13
The distribution property is the best justification.
50 degrees I’m guessing is the answer
Answer:
Step-by-step explanation: